Stroke after Coronary Artery Surgery: A Single Center Report - AlWaqfi, Nizar R.; Ibrahim, Khalid S. (International Journal of Angiology, 2014)
Stroke or cerebrovascular accident (CVA) is a devastating complication of coronary surgery. In this report, the incidence, and correlates of CVA following isolated coronary artery bypass grafting (CABG) surgery were evaluated. Data were collected retrospectively. Between 2006 and 2009, 855 patients underwent isolated CABG surgery. CVA was defined as any new neurological deficit lasting more than 24 hours. Univariate and multivariate analyses were utilized as appropriate. The incidence of CVA was 1.4% (n = 12). Age, previous CVA, and emergency surgery were correlated by univariate analysis. Multivariate analysis revealed age, previous CVA, and chronic renal impairment as predictors of CVA. Ten (83.3%) of the 12 patients were diagnosed to have CVA in the first 24 hours. Length of hospital stay was 20.9 ± 20.34 days for CVA patients and 9.2 ± 5.17 days for non-CVA patients (p ≤ 0.001). There were 4 (33.3%) deaths in CVA group and 27 (3.2%) for non-CVA patients (p = 0.001). Postoperative CVA is a major contributor to mortality, prolonged hospitalization, and other adverse postoperative complications. Further studies are needed to develop better strategies to minimize the occurrence of CVA among patients undergoing CABG.
Keywords: coronary bypass; complications; stroke; CVA; CABG surgery